PENERAPAN STRATEGI DIGITAL MARKETING CREATIVE AGENCY BUSINESS TO BUSINESS MELALUI MEDIA INSTAGRAM KINAJA INDONESIA - Sri Kurniasih Agustin; Nenik Diah Hartanti; Vely Randyantini; Helen Fitriana (Jurnal Abdimas Bina Bangsa, 2023)
B2B Creative Agency Digital Marketing strategy,  especially through Instagram media  , is one step to introduce products or services sold to the general public. The application of digital marketing  can help the company's marketing performance more efficiently and effectively. The purpose of writing this practical work is to find out the digital marketing strategy planning  of  one of  Kinaja Indonesia's creative agencies. The data collection method used in practical work activities is to conduct interviews and observations to find out information about activities that take place at Kinaja Indonesia. Kinaja Indonesia is a company engaged in creative industries such as videographics, web design, banner design, targeting large companies and even other government agencies. The digital marketing strategy carried out by Kinaja Indonesia is to implement the creation of social media platforms as a place to market the products / services offered, upload interactive content related to the services provided  by Kinaja Indonesia  , upload the results of products / services that have been created and display customer testimonials on a scheduled basis every week. This is used to increase sales and meet the needs and desires of consumers